A COMPREHENSIVE ANALYSIS OF ANTIDIABETIC DRUG INTERACTIONS IN GERIATRIC NON-INSULIN DEPENDENT DIABETES MELLITUS PATIENTS - YOSMAR, RAHMI; SHEPANY, EUGENIA; FITRIA, NAJMIATUL (International Journal of Applied Pharmaceutics, 2024)
Objective: Type 2 diabetes mellitus (DM) is a disease that is the leading cause of blindness, heart disease, and kidney failure. Geriatric patients with type 2 DM and complications require multiple medications (polypharmacy), contributing to drug-drug interactions (DDIs). DDIs can affect the clinical outcome of patients. This study aims to analyze potential drug-drug interactions based on the mechanism and severity, determine the relationship between the number of medications and potential drug interaction, and determine the relationship between polypharmacy and the severity of clinical outcomes. Methods: This was an analytical observational with retrospective data collection through patient medical records of hospitalized patients treated with an antidiabetic and one or more other drugs that met the inclusion criteria, involving 81 patients using total sampling. Results: The result showed that out of 81 patients, there were 59 patients who potentially experienced drug-drug interactions (72.8%) with a total of 162 cases of drug interactions, and the most prevalent interaction mechanism was pharmacodynamic (84.0%) with a moderate severity level (57.4%). There was a significant relationship between the number of medications and potential drug-drug interactions (p<0.05). At the same time, there was no meaningful relationship between polypharmacy and the severity of drug interactions with clinical outcomes (p>0.05). Conclusion: An increase in the number of drugs is a predictor of drug interactions. Although drug interactions may theoretically occur, not all interactions will significantly affect patients.